WATER WEAKENING OF CLINOPYROXENE IN THE DISLOCATION CREEP REGIME - Chen S.; Hiraga T.; Kohlstedt D.L. (My University, 2006)
We performed a series of triaxial compressive creep experiments at two different water fugacities to investigate the effect of water on the creep strength of a natural clinopyroxenite. Samples were deformed under water-saturated conditions at temperatures between 1373 and 1473 K, confining pressures of 150 and 300 MPa, and differential stresses from 34 to 261 MPa. Strain rates were in the range 10-7 to 10-5 s-1. Water fugacity was controlled at either 140 or 280 MPa. The creep results yield a stress exponent of 2.7 ± 0.3 and an activation energy of 670 ± 40 kJ/mol. Compared to dry clinopyroxene, wet samples creep over 100 times faster at a given temperature, confining pressure, water fugacity, and differential stress. The creep rate of clinopyroxene is proportional to the water fugacity to the 3.0 ± 0.6 power, with an activation volume of 0 m3/mol. One possible water-weakening mechanism is an enhancement of the rate of dislocation climb associated with increases in the concentration of jogs and the diffusivity of silicon ions. Compared to other major minerals in Earth's lower crust, specifically olivine and plagioclase, the water-weakening effect is most significant for clinopyroxene. Under hydrous conditions the strengths of clinopyroxene and anorthite are comparable over the investigated stress range, and both phases are weaker than olivine. Since the mineral assemblages in Earth's lower continental crust are often dominated by plagioclase and pyroxene, in places where a wet flow law applies, the mechanical behavior of clinopyroxene will have a substantial effect on creep strength. Copyright 2006 by the American Geophysical Union.